Research on the Impact of Short Video Content Marketing on Thailand Outbound Tourists’ Pre-trip Behavior Intention - Han , Dong; Wang, Shanshan (Journal of Roi Kaensarn Academi, 2023)
This paper aims to investigate the influential mechanism of Chinese short video platform content marketing on outbound Thai tourists’ pre-travel behavior intention by exploring the behavioral habits of tourists’ access to Thailand tourism information in short video platforms and the role of short video content platforms in tourists’ pre-travel. Chinese tourists who had been traveled to Thailand before selected as the research object. Based on the reviewing existing literature, this paper constructed a research framework, proposed research hypothesis, collected relevant data through using questionnaires, and analyzed 515 valid questionnaires with SPSS22.0 to draw the conclusions: short video content marketing positively promotes outbound Thai travelers’ implementation, planning, and recommendation intentions. The results contributes to the existing literature by providing a theoretical reference to the study of tourists’ pre-travel behavioral intentions and developing effective short-video content marketing strategies.